Морфологічні особливості будови вегетативних органів Camellia oleifera Abel - Kharchenko, I.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The results of studies of the morphological structure of the vegetative organs of Camellia oleifera Abel under greenhouse conditions are given. The peculiarities of morphological structure of root, shoot, buds and leaves are described. The characteristic features of vegetative organs C. oleifera are identified. The absence of pronounced terminal series of the leaves of the plants C. oleifera is revealed. The variability of the leaf blade form both between various individuals of the same species and within the single plant is detected. The presence of intermediate leaf forms between the lower leaf series to the middle one is identified. The presence of so called fish-like leaves is found. The essential similarity of the morphological structure of the vegetative organs of three Camellia species – C. oleifera, C. sasanqua and C. japonica is revealed. Significant differences between species studied, such as amount of the shoots, leaves and buds, the form of the leaves, the degree of indumentum of stems, leaves and buds are observed.